2024
DOI: 10.31234/osf.io/utp46
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Temporal Dynamics of Attitudinal Conflict in Daily Life: An Experience Sampling Study of Conflict Emergence and Resolution

Shiva Pauer,
Bastiaan T Rutjens,
Wilhelm Hofmann
et al.

Abstract: Although attitudinal conflict is a pervasive aspect of everyday decision-making, little is known about the temporal dynamics that characterize how people experience and resolve such conflict. The present research investigated attitudinal conflict by adopting a temporal framework of conflict emergence and resolution. We conducted a preregistered experience sampling study in the domain of meat consumption and employed a novel integrated sampling approach (of a total of 18,586 observations from 462 participants),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 147 publications
(271 reference statements)
0
6
0
Order By: Relevance
“…In fact, it is not only the mere existence of equally strong positive and negative attitudes that determines conflict magnitude; the magnitude of conflict increase when these attitude components are simultaneously accessible (McGregor et al, 2019). That is, felt ambivalence is experienced more strongly the faster people recall both their positive and negative evaluations and the stronger people report to elaborate on it (Itzchakov et al, 2020;Newby-Clark et al, 2002;Pauer et al, 2024). As attitudes inform people about their goals, we thus argue that strong and simultaneously accessible ambivalent attitudes elicit self-control conflicts: They inform people that an attitude object, such as a donut, aligns with their hedonic goals (to eat tasty food) and elicit corresponding cognitive, affective, and behavioral reactions, for instance the desire to approach the donut; however, they also inform them that the donut does not align with long-term goal (to stay slim and healthy) and elicit according responses such as restraint and avoidance.…”
Section: Attitude-based Self-control Conflictsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it is not only the mere existence of equally strong positive and negative attitudes that determines conflict magnitude; the magnitude of conflict increase when these attitude components are simultaneously accessible (McGregor et al, 2019). That is, felt ambivalence is experienced more strongly the faster people recall both their positive and negative evaluations and the stronger people report to elaborate on it (Itzchakov et al, 2020;Newby-Clark et al, 2002;Pauer et al, 2024). As attitudes inform people about their goals, we thus argue that strong and simultaneously accessible ambivalent attitudes elicit self-control conflicts: They inform people that an attitude object, such as a donut, aligns with their hedonic goals (to eat tasty food) and elicit corresponding cognitive, affective, and behavioral reactions, for instance the desire to approach the donut; however, they also inform them that the donut does not align with long-term goal (to stay slim and healthy) and elicit according responses such as restraint and avoidance.…”
Section: Attitude-based Self-control Conflictsmentioning
confidence: 99%
“…However, attitude change presumably happens incrementally over multiple consistent decisions (Buttlar, Pauer, & Harreveld, 2023), which might have made it difficult to observe these effects within the current study in which we only investigated the most intense conflict, reported at the end of each day. Thus, future research could rely on more fine-grained analyses that assess the effects of self-regulatory strategies more generally and attitude regulation more specifically over time (see, for instance, Pauer et al, 2024).…”
Section: Future Researchmentioning
confidence: 99%
“…Pauer et al (2022) showed that omnivores' felt ambivalence (but not potential ambivalence) increases when asking them to recall personally held positive and negative evaluations towards meat. A recent experience sampling suggests that everyday fluctuations in potential ambivalence about meat elicit felt ambivalence over time, especially during food choice (Pauer et al, 2024). In fact, Buttlar and Walther (2018) showed that meat-related ambivalence is reflected in people's movements when deciding whether different meat dishes are positive or negative.…”
Section: Disentangling the Meat Paradox 10mentioning
confidence: 99%
“…This includes information seeking on meat avoidance, presumably to facilitate behavioral change (Buttlar, Pauer, Ruby, et al, 2023;Pauer et al, 2022Pauer et al, , 2023. These motivational consequences might arise due to the high recurrence of meat-related ambivalence in omnivores (Pauer et al, 2023(Pauer et al, , 2024. In this way, people might reconcile their ambivalent attitude and overcome barriers to behavior change, such as the habit of meat consumption (Rees et al, 2018), as well as enhance the anticipated benefits of meat-free eating (de Boer & Aiking, 2017).…”
Section: What Are the Consequences Of Experiencing Meat-related Confl...mentioning
confidence: 99%
See 1 more Smart Citation